Adverse childhood experiences predict opioid relapse during treatment among rural adults. (September 2019) - Derefinko, Karen J.; Salgado García, Francisco I.; Talley, Kevin M.; Bursac, Zoran; Johnson, Karen C.; Murphy, James G.; McDevitt-Murphy, Meghan E.; Andrasik, Frank; Sumrok, Daniel D.
Abstract: Adverse childhood experiences (ACE) are a public health concern and strong predictor of substance abuse, but no studies to date have explored the association between ACE and opioid relapse during medication-assisted treatment. Using an observational design, we examined this relationship using archived medical records of 87 patients who attended opioid use disorder treatment (buprenorphine-naloxone and group counseling) at a rural medical clinic. All variables were collected from medical files. ACE scores were derived from a 10-item screening questionnaire administered at intake, a regular procedure for this clinic. The primary outcome was opioid relapse observed at each visit, as indicated by self-reported opioid use, positive urine drug screen for opioids, or prescription drug database results for opioid acquisition. The sample was 100% Caucasian and 75% male. A total of 2052 visit observations from the 87 patients were extracted from the medical records. Patients had an average of 23.6 ( SD = 22) treatment visits. Opioid relapse occurred in 54% of patients. Results indicated that for every unit increase in ACE score, there was an increase of 17% in the odds of relapse (95% CI: 1.05–1.30, p = .005). Additionally, each treatment visit was associated with a 2% reduction in the odds of opioid relapse (95% CI: 0.97–0.99, p = .008). We conclude that ACE may increase the risk for poor response to buprenorphine-naloxone treatment due to high rates of opioid relapse during the first treatment visits. However, consistent adherence to treatment is likely to reduce the odds of opioid relapse. Highlights: Relapses occurred in 54% of rural patients at an opioid use disorder clinic. Almost half of all participants reported four or more adverse childhood events. ACE score was related to an increase in the odds of relapse. Each treatment visit reduced the odds of opioid relapse. The highest relapse rate was on the first clinic visit.